2021
DOI: 10.1016/j.omto.2021.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell transcriptomics reveal DHX9 in mature B cell as a dynamic network biomarker before lymph node metastasis in CRC

Abstract: Increasing evidence indicates that mature B cells in the adjacent tumor tissue, both as an intermediate state, are vital in advanced colorectal cancer (CRC), which is associated with a low survival rate. Developing predictive biomarkers that detect the tipping point of mature B cells before lymph node metastasis in CRC is critical to prevent irreversible deterioration. We analyzed B cells in the adjacent tissues of CRC samples from different stages using the dynamic network biomarker (DNB) method. Single-cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 68 publications
(77 reference statements)
2
4
0
Order By: Relevance
“…Additionally, Liu et al. ( 20 ) found that DHX9 in mature B cell may be a dynamic network biomarker before lymph node metastasis in CRC, which may be consistent with our findings that DHX9 expression was remarkably associated with lymph node metastasis.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Additionally, Liu et al. ( 20 ) found that DHX9 in mature B cell may be a dynamic network biomarker before lymph node metastasis in CRC, which may be consistent with our findings that DHX9 expression was remarkably associated with lymph node metastasis.…”
Section: Discussionsupporting
confidence: 92%
“…The same results were obtained in HCC that the high DHX9 expression was obviously correlated with metastasis, vascular invasion, and TNM stage and was verified as an independent adverse prognostic indicator (19). Additionally, Liu et al (20) found that DHX9 in mature B cell may be a dynamic network biomarker before lymph node metastasis in CRC, which may be consistent with our findings that DHX9 expression was remarkably associated with lymph node metastasis.…”
Section: Discussionsupporting
confidence: 92%
“…We used Cytoscape software (version 3.7.1) to export the adjacency matrix for visualization and applied the CytoHubba plugin to perform a topological analysis, in which the node genes were ranked on the basis of their properties in the network, and then, the 100 genes with the highest rankings were visualized. 27 Transcription factor annotation AnimalTFDB (v3.0) is a database of 125,135 TFs and 80,060 transcription cofactors that are classi ed and annotated at the genome-wide level for 97 species, with various functions, such as transcription, and prediction of transcription factor-binding sites. In this study, we used human the TF database (HumanTFDB), an independent web interface, to annotate DNB genes to facilitate the analysis of the network regulatory relationships involving DNB genes.…”
Section: Ppi Network Analysismentioning
confidence: 99%
“…The DNB method has been used in studies in several elds for research into, for example, colorectal cancer metastasis, the epithelial-mesenchymal transformation and breast cancer. 21,22,23 Compared to traditional molecular biomarkers that are used to detect disease states on the basis of their differential molecular levels measured at a single time point, the DNB method integrates temporal information, and this case was chosen for its superiority in identifying the critical time before prepathological aggregation of the α-Syn state (the tipping point just before the dramatic transition from the physiological tetramer state to the pathological state of α-Syn aggregation). The DNB method revealed the key genes with changed expression before pathological aggregation of α-Syn and biomarkers useful for early diagnosis of diseases associated with the pathological aggregation of α-Syn, contributing to the study of the mechanisms underlying the pathological aggregation of α-Syn.…”
Section: Introductionmentioning
confidence: 99%
“…The main causes of T cell exhaustion were found to be the hub genes CCT6A and TUBA1B [ 15 ]. According to single-cell analysis of CRC adjacent tissue B cells, stage II was a crucial stage before lymph node metastasis, and the DHX9 gene participated in dynamic network changes during CRC development [ 16 ]. In addition, several research teams have applied the DNB method to examine lung metastasis in hepatocellular carcinoma, as well as irreversible alterations during cell differentiation [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%